2013
DOI: 10.1111/jgs.12198
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Older Age: Evidence from an Irish Cohort Study

Abstract: Increasing longevity can be associated with increasing QoL as long as it is accompanied by reasonable levels of mental and physical health, high-quality relationships, and social participation. Even if physical health becomes poor, evidence suggests that QoL can often remain high as individuals find value and enjoyment in other dimensions of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
67
2
16

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(101 citation statements)
references
References 18 publications
16
67
2
16
Order By: Relevance
“…The lower QoL scores observed among people aged 80+ have been linked to more impaired physical [3,7] and mental health [2], as well as to higher rates of widowhood, associated with depression [9].…”
Section: Description Of the Samplementioning
confidence: 99%
See 2 more Smart Citations
“…The lower QoL scores observed among people aged 80+ have been linked to more impaired physical [3,7] and mental health [2], as well as to higher rates of widowhood, associated with depression [9].…”
Section: Description Of the Samplementioning
confidence: 99%
“…Research in this field has found that older age is associated with a reduction in QoL, which appears to peak at 67 years, falling thereafter [2]. The most important factors reported to be associated with this decrease in QoL are health-related, including functional impairment and depression, as well as lifetime cumulative adversity [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Longitudinal studies are needed to investigate factors influencing HRQoL. Available longitudinal studies are based only on small numbers, [5][6][7][8][9][10][11] have short follow-up periods of 6-18 months, 5,6,8,9,11,12 and/or did not investigate the development of factors influencing HRQoL, but included the factors only at one fixed point in time.…”
Section: Introductionmentioning
confidence: 99%
“…In the elderly, QOL is affected by the many demanding situations and factors that are associated with older age -ranging from changes in health status to coping with new restrictions in life, and identifying new roles, opportunities, and available social support (Gurková, 2011). Demographic variables (age, gender, ethnicity), socio-economic characteristics (education, social status, income, social support...), cultural influences and values, health factors (health/medical condition, disease, functional status, health care services), and personal characteristics (e.g., coping mechanisms, self-efficacy...) can be considered to be predictors of QOL (Dragomirecká, Prajsová, 2009;Gurková, 2011;Bryła, Burzyńska, Maniecki-Bryła, 2013;Layte, Sexton, Savva, 2013;Bilgili, Arpaci, 2014;Chin, Lee, Lee, 2014;Forjaz et al, 2015).…”
Section: Introductionmentioning
confidence: 99%